How integration of the federal Indian Register has enhanced First Nations-specific analysis of ICES data - Schultz, Sue; Jones, Carmen; Walker, Jennifer (International Journal of Population Data Science, 2018)
Introduction In Ontario, First Nations are increasingly seeking population-level data about the health of their citizens. However, First Nations people are not readily identified in standard health administrative data and indirect strategies, such as the use of on-reserve addresses, are limited in scope and validity. Objectives and Approach The Chiefs of Ontario entered into a Data Governance Agreement with the Institute for Clinical Evaluative Sciences (ICES) that enabled the linkage of the federal Indian Register (IR) to data at ICES. This study examined the impact of the IR linkage on First Nations population estimates and location of residence, measured by postal code or residence code. Overall, and for each First Nation community in Ontario, we compared First Nations population estimates from the ICES data with and without the IR linkage to estimates available from Indigenous and Northern Affairs Canada (INAC). Results Without the IR, using only Ontario residence codes or postal codes that were unique to a given community, 62,242 individuals were identified as living in First Nations communities. This is approximately 30% lower than the current INAC on-reserve population estimate of 92,234 for First Nations communities in Ontario. Adding the IR allowed the use of non-unique postal codes as well, resulting in the identification of an additional 15,183 First Nations individuals. It also allowed the identification of over 113,000 First Nations individuals who live outside of First Nations communities, especially in urban areas. Finally, the combination of residence information and the IR permits communities to identify their registered member living within and outside their communities. Conclusion/Implications Using the IR in combination with geographic residence information, made possible through the Data Governance Agreement signed between Chiefs of Ontario and ICES, will provide First Nations communities with more accurate and complete population estimates, which is key to the production of useful and relevant First Nations-specific health research.